Dose-related Differences in the Pharmacodynamic and Toxicologic Response to a Novel Hyperglycosylated Analog of Recombinant Human Erythropoietin in Sprague-Dawley Rats with Similarly High Hematocrit. (April 2014) - Andrews, Dina A.; Boren, Babette M.; Turk, James R.; Boyce, Rogely W.; He, Yudong D.; Hamadeh, Hisham K.; Mytych, Daniel T.; Barger, Troy E.; Salimi-Moosavi, Hossein; Sloey, Bethlyn; Elliott, Steve; McElroy, Patricia; et al.
We recently reported results that erythropoiesis-stimulating agent (ESA)–related thrombotic toxicities in preclinical species were not solely dependent on a high hematocrit (HCT) but also associated with increased ESA dose level, dose frequency, and dosing duration. In this article, we conclude that sequelae of an increased magnitude of ESA-stimulated erythropoiesis potentially contributed to thrombosis in the highest ESA dose groups. The results were obtained from two investigative studies we conducted in Sprague-Dawley rats administered a low (no thrombotic toxicities) or high (with thrombotic toxicities) dose level of a hyperglycosylated analog of recombinant human erythropoietin (AMG 114), 3 times weekly for up to 9 days or for 1 month. Despite similarly increased HCT at both dose levels, animals in the high-dose group had an increased magnitude of erythropoiesis measured by spleen weights, splenic erythropoiesis, and circulating reticulocytes. Resulting prothrombotic risk factors identified predominantly or uniquely in the high-dose group were higher numbers of immature reticulocytes and nucleated red blood cells in circulation, severe functional iron deficiency, and increased intravascular destruction of iron-deficient reticulocyte/red blood cells. No thrombotic events were detected in rats dosed up to 9 days suggesting a sustained high HCT is a requisite cofactor for development of ESA-related thrombotic toxicities.